TYPES OF PROCESS IN CHILDREN’S SONG LYRICS OF NURSERY RHYMES - Lanayot Hutabalian and Elia MasaGintings (LINGUISTICA, 2015)
This study deals with types of process in children’s song lyrics of nursery rhymes.The objectives of the study were to find out the types of process used in children’ssong lyrics of nursery rhymes, to determine the dominant type of process used inchildren’s song lyrics and to describe the implication of types of process used inchildren’s song lyrics. This research was conducted by using descriptivequalitative research. The source of data was derived from children’s song lyrics ofnursery rhymes. The data were taken from the processes used in those song lyrics.There were 233 clauses in the children’s song lyrics of nursery rhymes. The resultof the analysis showed that all types of process used in children’s song lyrics ofnursery rhymes; material process with 124 clauses (53.22%) followed relationalprocess with 47 clause (20.17%), mental process with 25 clauses (10.73%), theverbal process with 24 clauses (10.30%), existential process with 11 clauses(4.72%) and behavioral process with 2 clauses (0.86%). The dominant types ofprocess used in children’s song lyrics of nursery rhymes are material process with124 occurrences. It means that in the song lyrics contain or told about activity,action or event that are happened or doing which happen outside the humanbeings.